1987
DOI: 10.1007/bf00016151
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair precedes replicative synthesis during early germination in maize

Abstract: DNA synthesis was studied during germination by following the rate of incorporation of radioactive thymidine into high molecular weight DNA. A peak of DNA synthesis was observed between the 8th and the 12th hour, i.e. before the beginning of the semi-conservative replication of genomic DNA, accompanied by an increase in the DNA content of the embryo. By the use of nucleoid sedimentation and nick-translation it was shown that, during the first hours of germination, extensive repair occurs of the DNA single-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…This result was found in two independent experiments and strongly suggests that the regulation of the expression of H4C13 differs from that of the other subfamilies during the DNA synthesis specific to the early steps of germinating maize embryos. It confirms previously published results showing that histones are actively synthesized during this period in germinating maize seedlings [ 14] in parallel to DNA synthesis related to extensive nuclear DNA repair [13]. One can imagine that the early synthesized histones could be 'repair histones', as most probably much damage occurring during dehydration and subsequent rehydration of the embryos during germination could also be repaired at the level of the nucleosome structure.…”
supporting
confidence: 76%
“…This result was found in two independent experiments and strongly suggests that the regulation of the expression of H4C13 differs from that of the other subfamilies during the DNA synthesis specific to the early steps of germinating maize embryos. It confirms previously published results showing that histones are actively synthesized during this period in germinating maize seedlings [ 14] in parallel to DNA synthesis related to extensive nuclear DNA repair [13]. One can imagine that the early synthesized histones could be 'repair histones', as most probably much damage occurring during dehydration and subsequent rehydration of the embryos during germination could also be repaired at the level of the nucleosome structure.…”
supporting
confidence: 76%
“…Villiers and Edgcumbe (1975) showed that if oxygen is present, fully hydrated seeds of lettuce (Lactuca sativa) are able to repair chromosomal aberrations, provided germination is prevented. Similarly, repair of DNA was detected prior to germination in imbibed seeds of maize (Zea mays; Zlatanova et al, 1987) and pea (Pisum sativum; Onelli et al, 2000) and in embryos of wild oat (Avena fatua) and rye (Secale cereale) (Elder and Osborne, 1993;Boubriak et al, 1997). Seeds that are not quite fully hydrated are also capable of repairing damage (Ibrahim and Roberts, 1983).…”
Section: Introductionmentioning
confidence: 98%
“…It was suggested that a beta-type DNA-polymerase might be responsible since the incorporation of (3H]-thymidine was resistant to the DNA polymerase-alpha inhibitor aphidicolin. DNA repair has also been demonstrated in pollen, embryos and root tips [5,12,42]. It is now well documented that higher plants are able to repair damages caused by UV, ionizing radiation or chemicals by mechanisms similar to those described for bacteria and mammalian cells [38].…”
Section: Introductionmentioning
confidence: 97%